2020
DOI: 10.1097/gme.0000000000001629
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with use of hormone therapy after preventive oophorectomy in BRCA mutation carriers

Abstract: Objective: Bilateral salpingo-oophorectomy (oophorectomy) is recommended to women with a germline BRCA1 or BRCA2 mutation before natural menopause to prevent ovarian and fallopian tube cancer. The adverse effects of early surgical menopause are well established. Although many of the side effects can be ameliorated by the use of hormone therapy (HT); use of HT in this group of predominantly young patients remains suboptimal. The goal of this study was to identify the frequency of HT use, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…32 However, overall uptake of ET is low in this population, potentially because the risks versus benefits of ET in highrisk women are not fully understood and safety concerns remain. 33 Strengths of this study include the prospective design and the comparison of premenopausal women undergoing RRBSO with premenopausal controls of a similar age, providing a meaningful comparison group. Additional strengths include the use of validated questionnaires that assessed several domains of sexual function and sexually related personal distress, and detailed prospective data on the use of ET.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 However, overall uptake of ET is low in this population, potentially because the risks versus benefits of ET in highrisk women are not fully understood and safety concerns remain. 33 Strengths of this study include the prospective design and the comparison of premenopausal women undergoing RRBSO with premenopausal controls of a similar age, providing a meaningful comparison group. Additional strengths include the use of validated questionnaires that assessed several domains of sexual function and sexually related personal distress, and detailed prospective data on the use of ET.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the benefits of ET are thought to outweigh the risks for younger premenopausal women undergoing RRBSO 32 . However, overall uptake of ET is low in this population, potentially because the risks versus benefits of ET in high-risk women are not fully understood and safety concerns remain 33 …”
Section: Discussionmentioning
confidence: 99%
“…Eligible study participants were identified from a longitudinal study of 17 947 women with a pathogenic or likely pathogenic germline variant in the BRCA1 or BRCA2 gene, which was initiated in 1995 and includes 83 participating centers from 16 countries. 2,[13][14][15][16] The women underwent genetic testing over an extended period of time . These women sought genetic testing because of a personal or family history of breast and/or ovarian cancer.…”
Section: Study Populationmentioning
confidence: 99%
“…(23) Women with deleterious mutations in the BRCA1 or BRCA2 genes undergoing prophylactic BSO may experience improved menopausal symptoms with hormone replacement. Mejia-Gomez et al (24) found that only 61% of these women under the age of 50 underwent hormone therapy. Estrogenic therapy in young women reduces the risk of vulvovaginal atrophy, osteoporosis, dyspareunia, atherosclerosis, cardiovascular disease and possibly dementia.…”
Section: Lynch Syndromementioning
confidence: 99%
“…Estrogenic therapy in young women reduces the risk of vulvovaginal atrophy, osteoporosis, dyspareunia, atherosclerosis, cardiovascular disease and possibly dementia. (24) In women with an intact uterus, adding progestogens to hormone therapy is recommended to prevent hyperplasia and endometrial carcinoma. (25) However, the use of progestogens has been associated with a higher risk of breast cancer in women with a BRCA1 mutation.…”
Section: Lynch Syndromementioning
confidence: 99%